Study on an on-line monitoring method for peak shaving capacity of thermal power unit - Zhu Lingkai; Wang Qian; Zhong Ziwei; Han Yue; Gong Zhiqiang; Zheng Wei; Shang Panfeng; Guo Junshan (E3S Web of Conferences, 2022)
Relying solely on pure condensing units can not meet the demand for power grid peak shaving, and thermoelectric units must also participate in peak shaving. In view of the dynamic change of peak shaving capacity of thermoelectric units with steam extraction, an on-line monitoring method of thermoelectric units is proposed in this paper. The upper and lower limits of peak shaving capacity of thermoelectric units under different steam extraction are calculated in real time, and the peak shaving capacity of thermoelectric units is evaluated on-line, so as to provide data support for scientific dispatching of power grid.